1025 PROGNOSTIC IMPACT OF STATINS AND DUAL ANTIPLATELET THERAPY ON LONG-TERM PROGNOSIS IN MINOCA PATIENTS. (15th December 2022) - Armillotta, Matteo; Sansonetti, Angelo; Bergamaschi, Luca; Stefanizzi, Andrea; Angeli, Francesco; Fabrizio, Michele; Amicone, Sara; Impellizzeri, Andrea; Suma, Nicole; Canton, Lisa; Bodega, Francesca; Fedele, Damiano; et al.
Abstract: Background: Myocardial Infarction with Non-Obstructive Coronary Artery disease (MINOCA) is a heterogeneous entity with relevant long-term major adverse cardiovascular events (MACE). There is solid evidence that secondary prevention strategies improve prognosis of patients with obstructive myocardial infarction. However, evidence-based treatments for MINOCA are lacking as no published randomized clinical trials have ever exclusively enrolled this population. In fact, treatment recommendations in current guidelines are mainly based on expert opinions and MINOCA patients are frequently discharged with statins and dual antiplatelet therapy (DAPT). Purpose: To evaluate the effects of statins and DAPT as secondary prevention treatments on long-term outcomes in MINOCA patients. Methods: We enrolled all consecutive MINOCA patients admitted to our Centre from 2016 to 2021. The diagnosis of MINOCA was made according to the current European Society of Cardiology diagnostic criteria (angiographic conventional cut-off of < 50% coronary stenosis without a clinically apparent alternative diagnosis). Second-level diagnostic work-up including cardiac magnetic resonance was performed to exclude non-ischemic troponin elevation cause. All-cause mortality and MACE (a composite of all-cause mortality, hospitalization for heart failure, myocardial re-infarction and stroke) were collected during follow-up. The prognostic impact of statins and DAPT at discharge was assessed. The relationship between treatments and outcomes was evaluated by using Kaplan-Meier survival analysis. Results: 278 MINOCA patients were enrolled, of whom 203 (73%) were discharged on statins and 123 (44.2%) on DAPT. After a median follow-up of 36 ± 14.8 months, the overall all-cause mortality was 11.8% and the composite endpoint (MACE) was achieved in 28.4% of the entire population. Kaplan-Meier curves showed that patients treated with statins had a significantly lower rate of all-cause mortality (9.3% vs 18.2%, p=0.04) and MACE (24.6% vs 39.2%, p=0.02). On the other hand, rates of death (9.8% vs 13.2%, p=0.4) and MACE (23.6% vs 31.6%, p=0.1) were similar in MINOCA patients treated with DAPT or single antiplatelet therapy. Conclusions: Among MINOCA patients, DAPT at discharge neither reduced long-term all-cause mortality nor MACE. In contrast, statin treatment provided beneficial effects on long-term outcomes. These results should be considered preliminary and require confirmation from randomized clinical trials.